Association between age-related hearing loss and depression: A systematic review and meta-analysis - Fuyao Li; Meiling Jin; Tianyi Ma; Chunlian Cui (PLoS ONE, 2025)
Introduction This meta-analysis examined the relationship between age-related hearing loss (ARHL) and depression in older adults, and further explored whether this relationship is moderated by age and gender. Methods We searched in 4 English databases: PubMed, Embase, Web of Science, and Cochrane Library. Ultimately, we identified 9 studies, involving 3 cohort studies and 6 cross-sectional studies. We used Hedges’ g as the effect size, and all pooled analyses were performed using random-effects models. Results ARHL patients had higher depressive symptom scores than non-ARHL older adults (g = 0.52). When divided into subgroups based on study type, a large effect size was demonstrated in the cross-sectional study group (g = 0.68) and was not statistically different in the cohort study group (g = 0.06). Meta-regression results showed that the effect size of depression in older adults with ARHL was significantly associated with the percentage of females (t = 5.97, p = 0.000) and not significantly associated with age (t = 0.94, p = 0.364). Conclusions Patients with ARHL are more likely to be depressed than older adults with normal hearing, and this relationship is influenced by the gender of the patients.